Challenges in Pre hospital emergency medical service in Mashhad: A qualitative study - roghieh bayrami; hossein ebrahimipour; alireza rezazadeh (Tehran University of Medical Sciences, 2017)
Background: Pre hospital emergency medical service (EMS) as the first line of emergency care and treatment in the out- of -hospital has a considerable importance in the health care system. Planning on finding about strengths and weaknesses and improve the quality of EMS by exploring the problems of this section has considerable important.This study aimed to explore the challenges of pre hospital emergency medical service in Mashhad. Materials and methods: A qualitative study was done with 14 personnel working in EMS sites in Mashhad using purposeful sampling. Data was collected by semi structured interview and analyzed using conventional content analysis approach according to Graneheim and Lund man 2004 with ATLAS.ti  software. Results: Three general themes were identified including 1) "challenges in Human resources"( Individual characteristics of human resources and personnelchr('39')s dissatisfaction 2) "challenges in organization" (Structural challenges, lake of equipment and human resource limitation 3) "socio-cultural challenges"(Environmental-social challenges and cultural challenges) were determined. Conclusion: personnelchr('39')s dissatisfaction, structural challenges, human resource limitation, lake of equipment   and Environmental-social challenges were the most important challenges in pre-hospital emergency system. Organizational independence , create organizational rows, regulation of laws and administrative regulations reform in relation to the range of services offered by emergency personnel, attention to the facilities and cooperation And the participation of other organizations, such as media and traffic to enhance pre-hospital emergency services at the community level can be effective in reducing the challenges in hospital emergency system.